Krüppel-Like Factor 4 Overexpression Initiates a Mesenchymal-to-Epithelial Transition and Redifferentiation of Human Pancreatic Cells following Expansion in Long Term Adherent Culture. - Kenneth R Muir; Maria João Lima; Hilary M Docherty; Neil W A McGowan; Shareen Forbes; Yves Heremans; Stuart J Forbes; Harry Heimberg; John Casey; Kevin Docherty (PLoS ONE)
A replenishable source of insulin-producing cells has the potential to cure type 1 diabetes. Attempts to culture and expand pancreatic β-cells in vitro have resulted in their transition from insulin-producing epithelial cells to mesenchymal stromal cells (MSCs) with high proliferative capacity but devoid of any hormone production. The aim of this study was to determine whether the transcription factor Krüppel-like factor 4 (KLF4), could induce a mesenchymal-to-epithelial transition (MET) of the cultured cells. Islet-enriched pancreatic cells, allowed to dedifferentiate and expand in adherent cell culture, were transduced with an adenovirus containing KLF4 (Ad-Klf4). Cells were subsequently analysed for changes in cell morphology by light microscopy, and for the presence of epithelial and pancreatic markers by immunocytochemistry and quantitative RT/PCR. Infection with Ad-Klf4 resulted in morphological changes, down-regulation of mesenchymal markers, and re-expression of both epithelial and pancreatic cell markers including insulin and transcription factors specific to β-cells. This effect was further enhanced by culturing cells in suspension. However, the effects of Ad-KLf4 were transient and this was shown to be due to increased apoptosis in Klf4-expressing cells. Klf4 has been recently identified as a pioneer factor with the ability to modulate the structure of chromatin and enhance reprogramming/transdifferentiation. Our results show that Klf4 may have a role in the redifferentiation of expanded pancreatic cells in culture, but before this can be achieved the off-target effects that result in increased apoptosis would need to be overcome.